Transient analysis of impatient customers in an M/M/1 disasters queue in random environment. Issue 6 (10th February 2020) - Ammar, Sherif I.; Jiang, Tao; Ye, Qingqing
Abstract : Purpose: This paper aims to consider a single server queue with system disasters and impatience behavior are evident in our daily life. For this purpose, authors require to know the general behavior of these systems. Transient analysis shows for us how the system will operate up to some time instant t . Design/methodology/approach: In this paper, authors consider a single server queue with system disaster and impatient behavior of customers in a multi-phase random environment, in which the system transits to a repair state after each system disaster. When the system is in a failure phase or going through a repair phase, the new arrivals would be impatient. In case the system is not repaired before the customer's time expires, the customer would leave the queue and never return. Moreover, after repair, the system becomes ready for service in an operative phase with probability q_i 0.. Using generating functions along with continued fractions and some properties of the confluent hypergeometric function, authors obtained on their own results. Findings: Explicit expressions have been obtained for the time-dependent probabilities of the underlying queuing model. Also, time-dependent mean and variance of customers in the system are deduced. Research limitations/implications: The system authors are dealing with is somewhat complicated, there are some performance measures that cannot be achieved, but some of them have been obtained, such as the expectation and variance of the number of customers in the system. Practical implications: Based on the obtained results, some numerical examples are some numerical examples are presented to illustrate the effect of various parameters on the behavior of the proposed system. Social implications: Authors' studied transient analysis of a single server queue with system disaster and impatient customer system is suitable for behavior interpretation of many systems in our lives, such as telecommunication networks, inventory systems and impatient telephone switchboard customers, manufacturing system and service system. Originality/value: To the best of the author's/authors' knowledge and according to the literature survey, in a multi-phase random environment, no previous published article is presented for transient analysis of a single server queue with system disaster and impatient customer behavior in a random environment.